2014
DOI: 10.5152/tjg.2014.6579
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of WHO 2000 and WHO 2010 classifications of gastroenteropancreatic neuroendocrine tumors

Abstract: Background/Aims: Grading and staging are important in gastroenteropancreatic neuroendocrine tumors for directing treatment. In this study, we evaluated the histopathological parameters of gastroenteropancreatic neuroendocrine tumors and statistically analyzed the correlations of these parameters between the World Health Organization (WHO) 2000 and 2010 classifications. Materials and Methods: A total of 77 cases diagnosed as neuroendocrine tumors were included in the study. Cases were classified according to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 17 publications
1
13
0
1
Order By: Relevance
“…In our series of GEP-NENs, the proportions of G1/G2/G3 were 63.3/16.3/20.4 %, respectively. These are very comparable to the results of other reports that classify their cases as proportions of G1/G2/G3; these are 64.9-73.2/6.3-10.5/16.3-24.7 %, respectively [18][19][20]. The most common type of lung NEN is reported to be SCC, which accounts for 60-80 % of pulmonary NENs and, together with another highly malignant NEN, LCNEC, represents over 80 %; in comparison, two lung NENs with low-to intermediate-grade malignancy (typical and atypical carcinoids) represent less than 20 % [21][22][23].…”
Section: Discussionsupporting
confidence: 90%
“…In our series of GEP-NENs, the proportions of G1/G2/G3 were 63.3/16.3/20.4 %, respectively. These are very comparable to the results of other reports that classify their cases as proportions of G1/G2/G3; these are 64.9-73.2/6.3-10.5/16.3-24.7 %, respectively [18][19][20]. The most common type of lung NEN is reported to be SCC, which accounts for 60-80 % of pulmonary NENs and, together with another highly malignant NEN, LCNEC, represents over 80 %; in comparison, two lung NENs with low-to intermediate-grade malignancy (typical and atypical carcinoids) represent less than 20 % [21][22][23].…”
Section: Discussionsupporting
confidence: 90%
“…LVI was described as having uncertain malignant potential in the WHO 2000 classification [23], and previous reviews proposed it as a risk factor for metastasis in D-NETs [6,24,25]. However, the WHO 2010 classification did not regard this as a prognostic factor possibly because of enormous inter-observer differences among pathologists in identifying the presence of LVI [1,26]. However, the recent study showed that LVI is one of the risk factors for LN metastasis in D-NET [21].…”
Section: Discussionmentioning
confidence: 99%
“…Pattern and risk factors for distant metastases in gastrointestinal neuroendocrine neoplasms: a populationbased study neuroendocrine carcinoma (NEC) based on the morphology and proliferation rate [4,5]. It is generally acknowledged that survival is better for NET than for NEC.…”
Section: Original Researchmentioning
confidence: 99%
“…The most recent 2010 WHO system has defined all neuroendocrine tumors (NETs) as neoplasms with malignant potential, and the acronym NEN is recommended to corresponding to the term neuroendocrine neoplasia. NENs are currently classified as either well‐differentiated (low‐grade to intermediate‐grade) neuroendocrine tumors (NET) or poorly differentiated (high‐grade) neuroendocrine carcinoma (NEC) based on the morphology and proliferation rate . It is generally acknowledged that survival is better for NET than for NEC.…”
Section: Introductionmentioning
confidence: 99%